2011
DOI: 10.1007/s11999-011-1864-4
|View full text |Cite
|
Sign up to set email alerts
|

Three- and Four-part Fractures Have Poorer Function Than One-part Proximal Humerus Fractures

Abstract: Background Locking plates have become a commonly used fixation device in the operative treatment of three-and four-part proximal humerus fractures. Examining function in patients treated nonoperatively and operatively should help determine whether and when surgery is appropriate in these difficult-to-treat fractures. Questions/purposes We compared functional scores, ROM, and radiographs in patients with one-part proximal humerus fractures treated nonoperatively to those in patients with displaced three-and fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…3,30 This also explains why QoL is lower when impairment affects the lower extremity. 7,27,29 We were able to show the influence on all scores by the patients' age, sex, and time of follow-up, and by the different fracture types. Multivariate regression analysis showed that a patient's age influenced the score more than fracture type.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…3,30 This also explains why QoL is lower when impairment affects the lower extremity. 7,27,29 We were able to show the influence on all scores by the patients' age, sex, and time of follow-up, and by the different fracture types. Multivariate regression analysis showed that a patient's age influenced the score more than fracture type.…”
Section: Discussionmentioning
confidence: 78%
“…Values above the US norm 12 were also documented in recently published literature comparing 3-and 4-part PHF with conservative treatment of 1-part fractures in a US cohort. 7 Furthermore, while both genders were almost equally distributed in the youngest group (A), there was an increasing dominance of females with rising age, which makes an average difference of approximately 4 points related to the gender in group D. We were not able to adjust the SF-36 accordingly, while it was possible to adapt the CMS for age and gender. 22 Unfortunately, a corresponding European norm for such comparisons is unavailable.…”
Section: Limitationsmentioning
confidence: 91%
See 1 more Smart Citation
“…Locking plates have been successfully introduced in the treatment of proximal humerus fractures. [19][20][21][22] However, failure rates of up to 14% highlight the fact that not all problems associated with the treatment of this demanding type of fracture have been fully solved. 2,23,24 In addition to the general presence of osteoporosis, the local distribution of BMD within the humeral head may have a significant effect on the primary stability of an osteosynthesis because it remains unclear in what quality of bone stock within the humeral head the screws of a locking plate purchase and whether the areas with good bone quality are even reached by the screws.…”
Section: Discussionmentioning
confidence: 99%
“…Proximal humeral fracture accounts for 4–5% of all bone fractures, with the growing elderly population, the frequency is still increasing [ 1 3 ]. Roughly 20% of these fractures exhibit an unstable fracture pattern, which should be treated by surgery [ 4 ]. Numerous operative techniques have been used for fixing unstable fractures, including Kirschner wires, tension band sutures, intramedullary nails, prosthetic replacement and locking plates.…”
Section: Introductionmentioning
confidence: 99%